Incidence of cesarean section by maternal desire before and after the State Law nº 20.127 in the 10th Health Region of Paraná (Research, Society and Development, 2024)
Introduction: Cesarean section rates continue to grow unstoppably due to sociocultural, ethical, bioethical, medical and political factors, but when performed indiscriminately it can generate negative consequences for the maternal-fetal binomial. State Law No. 20,127/2020 of Paraná or Law on cesarean section at maternal request, makes it possible for pregnant women in the SUS, even without clinical indications, to opt for an elective cesarean section. Objective: Quantify the incidence of elective cesarean sections and cesarean sections on request before and after the sanction of the Law in the 10th Health Region of the State of Paraná. Methods: Retrospective cross-sectional study model, with a quantitative approach and based on documentary analysis. Results: It is shown that in 2019, births through the SUS totaled 5,026, of which 61.1% were vaginal births and 37.9% were cesarean sections due to medical indication. In relation to the year 2023, the year in which the Law was already in force, births through the SUS totaled 5,021, corresponding to 51.5% vaginal births and 48.5% cesarean sections, 23.2% of which were elective cesarean births due to desire maternal. Conclusion: Despite the increase in cesarean birth rates being a global trend, State Law No. 20,127/2020 of Paraná contributes to this growing disorder that puts the maternal-fetal binomial at risk. Therefore, more studies on the topic are needed with longitudinal analyzes and other variables such as long-term complications from excessive cesarean sections.